A Narrative Review: Redefining Meniere’s Disease Diagnosis in the Era of Precision Medicine - Sulistyani Sulistyani; Firdha Latifatun Nasywa; Marsyanda Maisie Salsabila; Salma Zakiyatusholihat; Zahra Maha Dewi; Muhammad Hafidz Erlangga (Sean Institute, 2025)
Ménière’s disease (MD) is a chronic inner ear disorder marked by recurrent vertigo, tinnitus, aural fullness, and sensorineural hearing loss. It represents 7–8% of vertigo cases in outpatient settings and often leads to significant disability. The absence of a gold standard diagnostic test remains a challenge for accurate and timely diagnosis. A narrative review was conducted in line with Scale for the Quality Assessment of Narrative Review Articles (SANRA) guidelines. Literature searches were performed in PubMed, ScienceDirect, and Google Scholar using the terms (“Meniere's Disease” OR “Vertigo” OR “Auditory”) AND (“diagnostic examination” OR “diagnostic test”), limited to the last 10 years. Eligible studies were human research evaluating diagnostic methods for MD, available in full text. Nine studies met inclusion criteria: three observational cohort, four retrospective study, two prospective study, one structured review. Diagnostic methods assessed included audiometry, Vestibular Evoked Myogenic Potentials (VEMP), Electrocochleography (ECochG), Video Head Impulse Test (vHIT), and hydrops-sensitive Magnetic Resonance Imaging (MRI). Among these, MRI emerged as the most promising technique for early and reliable diagnosis. MD is a multidimensional condition involving auditory, vestibular, and neuropsychological systems. Hydrops MRI holds strong potential as a future diagnostic standard, but further multicenter validation is required before its widespread clinical adoption.